The neural bases of distracter-resistant working memory - Wager, Tor D. (2014)
A major difference between humans and other animals is our capacity to maintain information in working memory (WM) while performing secondary tasks, which enables sustained, complex cognition. A common assumption is that the lateral prefrontal cortex (PFC) is critical for WM performance in the presence of distracters, but direct evidence is scarce. We assessed the relationship between fMRI activity and WM performance within-subjects, with performance matched across Distracter and No-distracter conditions. Activity in ventrolateral PFC during WM encoding and maintenance positively predicted performance in both conditions, whereas activity in the pre-supplementary motor area (pre-SMA) predicted performance only under distraction. Other parts of dorsolateral and ventrolateral PFC predicted performance only in the No-distracter condition. These findings challenge a lateral PFC-centered view of distracter-resistance, and suggest that the lateral PFC supports a type of WM representation that is efficient for dealing with task-irrelevant input but is nonetheless easily disrupted by dual-task demands.